The impact of earnings expectations on corporate downsizing - Schulz, Ann-Christine; Wiersema, Margarethe F. (Strategic Management Journal, 2018)
[Research summary: We propose that due to financial market pressures, managers are forward-looking in their search and decision processes and focus on meeting performance targets set by the financial community. Using panel data on S&P 100 companies, we find that pressure felt by management to meet the analyst consensus earnings estimate influences the extent of corporate downsizing. Moreover, our results show that high levels of institutional investor stock ownership and CEO power attenuate managers' sensitivity to financial market pressures, while high levels of analyst coverage increase their sensitivity. Managerial summary: In this study we examine how financial market pressures influence managers' downsizing decisions. We argue that investment analysts' earnings estimates represent important performance targets to which managers aspire. If firms fail to meet analysts' expectations, the stock price will suffer. This study shows that managers utilize corporate downsizing to address the potential shortfall between a firm's future performance and the analyst consensus earnings estimate. In addition, we find that managers' concerns over meeting analysts' earnings estimates are influenced by various contextual factors such as institutional investor stock ownership, CEO power, and high levels of analyst coverage.]